2017
DOI: 10.1055/s-0037-1603363
|View full text |Cite
|
Sign up to set email alerts
|

Inferior Vena Cava Agenesis and Deep Vein Thrombosis in the Young: A Review of the Literature and Local Experience

Abstract: Congenital agenesis of the inferior vena cava (AIVC) is a rare vascular abnormality with a prevalence of 0.0005 to 1% in the general population. This condition is found in almost 5% of young patients (younger than 30 years) with proximal, typically bilateral, deep venous thrombosis (DVT) of the lower limbs, often in the absence of apparent risk factors. However, AIVC in young patients with DVT is probably underestimated because AIVC cannot be detected by the standard DVT diagnostic workup. Inherited thrombophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Conservative therapy with anticoagulation, compression stockings and management of complications seem to be the mainstay of treatment, but invasive surgical interventions with an endovascular approach or even prosthetic replacement of the IVC have also been reported, with successful results [1,5] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservative therapy with anticoagulation, compression stockings and management of complications seem to be the mainstay of treatment, but invasive surgical interventions with an endovascular approach or even prosthetic replacement of the IVC have also been reported, with successful results [1,5] .…”
Section: Discussionmentioning
confidence: 99%
“…Congenital malformation and agenesis of the inferior vena cava (IVC) are extremely rare vascular anomalies, being present in only 0.0005–1% of the general population [1] . The absence of the infra-renal segment of IVC seems to be the rarest anomaly [2,3] , with KILT syndrome (kidney anomaly, IVC anomaly and leg thrombosis) also beingvery uncommon [1] . Frequently, these are incidental findings on imaging studies but have been reported during abdominal surgery or when difficulties arise during femoral catheterization.…”
Section: Introductionmentioning
confidence: 99%
“…Given the rarity of IVC agenesis, there are no clinical trials to determine the best treatment strategy 5 . The mainstay of treatment is conservative; lifelong warfarin anticoagulation to prevent venous thrombosis or recurrence is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of AVCI may be overlooked as ultrasonography might miss the diagnosis. High level of suspicion for AVCI and further investigation with CT/MRI angiography is needed in young patients with DVT, particularly bilateral, with or without the presence of other obvious cause for DVT [2,4]. There are two main hypotheses for the etiology of AVCI.…”
Section: Introductionmentioning
confidence: 99%
“…Three main types of AVCI have been described: agenesis of the suprarenal IVC, which is associated with cardiac and visceral anomalies (type 1), absence of the infrarenal IVC (type 2), and absence of the entire IVC, which results from failure in development of all three vein systems and is not associated with other congenital anomalies (type 3). According to the second hypothesis, AVCI is the result of intrauterine or perinatal thrombosis [1][2][3]6].…”
Section: Introductionmentioning
confidence: 99%